Ganz Osteotomy for Adolescent and Young Adults with Acetabuler Dysplasia. (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional and radiological outcome of Ganz osteotomy for the treatment of acetabular dysplasia (AD) in adolescent and young adults.Methods: This descriptive study was conducted in Department of Orthopaedics and Traumatology Alt?nbas University Medical Faculty Istanbul Turkey from 2nd February 2013 to 2nd January 2022.All adolescent and young adults with acetabular dysplasia(AD) fulfilling the inclusion criteria were operated with Ganz osteotomy(Bernese).Post operative functional results were assesses with Merle d’Aubigne Hip Score and gradded as excellent(score 15-17) good(12-14,average(11-13) and poor(